Early Neuropsychological Characteristics of Progranulin Mutation Carriers. (4th July 2014) - Hallam, Bradley J.; Jacova, Claudia; Hsiung, Ging-Yuek R.; Wittenberg, Dana; Sengdy, Pheth; Bouchard-Kerr, Phoenix; Slack, Penny; Rademakers, Rosa; Baker, Matthew; Chow, Tiffany W.; Levine, Brian; Feldman, Howard H.; et al.
Abstract Mutations in the progranulin gene (GRN) are a common cause of familial frontotemporal dementia. We used a comprehensive neuropsychological battery to investigate whether early cognitive changes could be detected in GRN mutation carriers before dementia onset. Twenty-four at-risk members from six families with known GRN mutations underwent detailed neuropsychological testing. Group differences were investigated by domains of attention, language, visuospatial function, verbal memory, non-verbal memory, working memory and executive function. There was a trend for mutation carriers (n=8) to perform more poorly than non-carriers (n=16) across neuropsychological domains, with significant between group differences for visuospatial function (p<.04; d=0.92) and working memory function (p<.02; d=1.10). Measurable cognitive differences exist before the development of frontotemporal dementia in subjects with GRN mutations. The neuropsychological profile of mutation carriers suggests early asymmetric, right hemisphere brain dysfunction that is consistent with recent functional imaging data from our research group and the broader literature. (JINS, 2014, 20, 1–10)